COMMUNICATION TECHNOLOGY INNOVATION IN THE DEVELOPMENT OF LEARNING MEDIA THROUGH THE APPLICATION OF MEDIA RELEVANCE THEORY : Inovasi Teknologi Komunikasi dalam Pengembangan Media Pembelajaran Melalui Penerapan Teori Relevansi Media - Ardini, Muhammad Dimas; Maulidia, Via; Anbiya, Bakti (Program Studi Teknologi Pendidikan FKIP Universitas Ibn Khaldun, Bogor, 2024)
In the ever-growing digital era, communication technology innovation is crucial to facilitate the effective exchange of various information. Media relevance theory offers a powerful framework for understanding how messages are appropriately delivered and received by recipients. However, the implementation of this theory in the context of communication technology innovation has not been fully explored. This research aims to explore the application of media relevance theory to communication technology innovation in media development. The research method used is a systematic literature review (SLR). The SLR method is used to identify, review, evaluate and interpret all existing research using practical areas of interest, using relevant and proprietary research questions. By using the SLR approach, systematic reviews and journal identification can be carried out, with each process following predetermined steps or protocols. The research results show that: 1) communication technology that pays attention to the principles of media relevance theory tends to be more effective and accepted by users. 2) communication technology in developing learning media through the application of media relevance theory. 3) media relevance theory can be applied effectively to increase communication technology innovation in the development of learning media. 4.) obstacles that may occur in applying media relevance theory to increase communication technology innovation in the development of learning media. 5) comparing the use of media relevance theory with other approaches. By applying this theory, developers can create more satisfying communication experiences. These findings provide better insight into the development of learning media and its importance for communication technology developers in designing innovative solutions.